2014
DOI: 10.1021/am5025963
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Photocurrent Density of p-Type Solar Cells Based on Organometal Halide Perovskite-Sensitized Mesoporous NiO Photocathodes

Abstract: The p-n tandem design of a sensitized solar cell is a novel concept holding the potential to overcome the efficiency limitation of conventional single-junction sensitized solar cells. Significant improvement of the photocurrent density (Jsc) of the p-type half-cell is a prerequisite for the realization of a highly efficient p-n tandem cell in the future. This study has demonstrated effective photocathodes based on novel organometal halide perovskite-sensitized mesoporous NiO in liquid-electrolyte-based p-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 48 publications
0
32
1
1
Order By: Relevance
“…In addition to semiconducting n-type materials, p-type semiconductors, mainly NiO, can also be used to fabricate mesporous scaffolds [114,115]. In this configuration, a compact layer and mesoporous scaffold based on NiO are subsequently deposited onto a FTO substrate, establishing a hole transport pathway.…”
Section: The Mesoporous Scaffoldmentioning
confidence: 99%
“…In addition to semiconducting n-type materials, p-type semiconductors, mainly NiO, can also be used to fabricate mesporous scaffolds [114,115]. In this configuration, a compact layer and mesoporous scaffold based on NiO are subsequently deposited onto a FTO substrate, establishing a hole transport pathway.…”
Section: The Mesoporous Scaffoldmentioning
confidence: 99%
“…Além disso, possui alto custo, dificultando sua utilização comercial. 116,117 Desse modo, materiais como poli-triarilamina (PTAA), 78,114,118 poli(3-hexiltiofeno)(P3HT), [119][120][121][122] poli[N-900-heptadecanil-2,7-carbazol-alt-5,5-(40,70-di-2--tienil-20,10,30-benzotidiazol)] (PCDTBT), 78 NiO, [123][124][125] CuSCN, [126][127][128][129] CuI, 130,131 entre outras diversas moléculas orgânicas, têm sido estudados para a substituição do spiro-MeOTAD. 36,74,104,132 A Figura 10 apresenta alguns dos HTLs e ETLs recentemente utilizados em células solares de perovskitas e os seus respectivos níveis energéticos.…”
Section: Desenvolvimento Das Células Solares De Perovskita Progressosunclassified
“…Tian et al [126] reported an efficiency of 0.16 % while Wang et al [127] were able to achieve up to 0.71% (0.91% at reduced light intensity). These first reports used MALH in a manner analogous to that reported in 2011 by the group of Nam-Gyu Park [128], and brought the material to the attention of the solar cell community.…”
Section: Inorganic Sensitizersmentioning
confidence: 99%